Linear Factor Models in Finance - Knight, John L.; Satchell, Stephen (Amsterdam; Oxford: Elsevier Butterworth-Heinemann, 2005)
The determination of the values of stocks, bonds, options, futures, and derivatives is done by the scientific process of asset pricing, which has developed dramatically in the last few years due to advances in financial theory and econometrics. This book covers the science of asset pricing by concentrating on the most widely used modelling technique called: Linear Factor Modelling.
Includes bibliographical references and index.
rpm 05/09/13
Loans
Keywords: Finance -- Mathematical models